PECULIARITIES OF PERCEPTION BY MOSCOW STUDENT YOUTH OF THE PROCESS OF MARKETING COMMUNICATION OF ONLINE PURCHASES - I. Yu. Alexandrova (Вестник университета, 2019)
The problem of communicative efficiency of the Russian online stores in the context of current trends in development of electronic commerce in Russia has been considered. The empirical study, conducted by the author, aimed to identify the features of perception by Moscow student youth of marketing communication process of online purchase, has been described. In the process of achieving this aim following circumstances have been revealed: 1) the frequency of purchases of goods and services by students in online stores; 2) the reasons for low purchasing activity in online stores, as well as the complete rejection of online shopping; 3) typical goods/services, the purchase of which is carried out in online stores; 4) characteristic communicative failures of the online shopping process, which are the cause of psychological discomfort of a young online buyer. The obtained results of the study can be used by the Russian developers of online stores in order to improve efficiency of marketing web communication process.